UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PROGRAM LINEAR MELALUI MODEL PEMBELAJARAN EXPOSITORY LEARNING DI KELAS XI MIPA-1 SMA NEGERI 1 SARIWANGI - Dede Kurnia (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
The problem currently faced by teachers at SMA Negeri 1 Sariwangi is students' mastery of linear programming material, especially in remembering concepts in a limited time that have been taught. Although at the end of the provision of the material has shown the mastery of learning, but when viewed from the achievement of learning objectives, this is far from what is actually expected. This is evident from the results of learning mathematics in the previous linear program material which only reached 73 while "the minimum completeness criteria for mathematics subjects at SMA Negeri 1 Sariwangi was 80". The objectives of this Classroom Action Research (CAR) are: To determine the improvement of student learning outcomes on the subject of linear programming through expository learning learning models in Class XI MIPA-1 SMA Negeri 1 Sariwangi. The method used in this research, namely Classroom Action Research (CAR), is a form of action research that is carried out directly in the classroom. The conclusions obtained based on the discussion of the research results, are as follows: The teacher's ability to make lesson plans about the students' abilities in the linear programming subject in Class XI MIPA-1 SMA Negeri 1 Sariwangi, obtained the following results: Learning Implementation Plans for the first cycle with an average 3.08 in the good category, the second cycle lesson plan is 3.45 in the good category. The process of implementing learning about the ability of students on the subject of linear programming in Class XI MIPA-1 SMA Negeri 1 Sariwangi, obtained the following results: The average ability of teachers in the first cycle with an average of 3.3 with a good category, the second cycle with an average an average of 3.6 with good category. Student learning outcomes after using the expository learning model in learning mathematics, obtained a score in the first cycle the average value of 77 with a poor category, the second cycle of 82 with a very good category.